2019
DOI: 10.1142/s2282717x19400012
|View full text |Cite
|
Sign up to set email alerts
|

The Peculiarity of the Cooperative and Mutual Model: Evidence From the European Banking Sector

Abstract: The crucial role of mutual banks in promoting local development is highlighted by an extensive theoretical and empirical literature. The historical success of mutual banks derives not only from their specific business model, but also from their peculiar and distinguishing corporate governance with member ownership. According to a copious literature, these features have probably allowed mutual banks to better withstand financial crisis. This work compares the cost efficiency of European mutual banks by analyzin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Groeneveld (2016) came to the same conclusion for the Netherlands. Paceli et al (2019) in a study of mutual banks in Italy, Germany, France, and Spain, concluded that European mutual banks have a higher degree of efficiency than commercial banks. Efficiency is related to the efficiency of traditional lending, the degree of prudence in provisioning for credit risks, and the level of liquidity.…”
Section: Literature Review Of Crisis Results Over the Banking Systemsmentioning
confidence: 99%
“…Groeneveld (2016) came to the same conclusion for the Netherlands. Paceli et al (2019) in a study of mutual banks in Italy, Germany, France, and Spain, concluded that European mutual banks have a higher degree of efficiency than commercial banks. Efficiency is related to the efficiency of traditional lending, the degree of prudence in provisioning for credit risks, and the level of liquidity.…”
Section: Literature Review Of Crisis Results Over the Banking Systemsmentioning
confidence: 99%
“…Makinen and Jones, 2015; Spulbar, Nitoi and Anghel, 2015). Recently, Pacelli, Pampurini and Labini (2019) have compared the cost efficiencies of cooperative and commercial banks in Italy, Germany, France and Spain between 2011 and 2016, thus capturing the European sovereign debt and NPL crises. They find that the business model of cooperative and mutual banks is strong during bad times, exhibiting higher efficiency levels than commercial banks.…”
Section: Literature and Hypothesis Developmentmentioning
confidence: 99%
“…By improving screening and monitoring of borrowers, these features enhance the efficiency and effectiveness of credit cooperatives to serve marginal borrowers (Grillo, 2013). According to Pacelli et al (2019), mutual banks' ability to assess risks accurately results from territorial proximity, which allows local savings to be collected. Part of the profits of mutual banks are reinvested back into the community to promote the sustainable development of their territories.…”
Section: Mutual Cooperative and Profitoriented Banksmentioning
confidence: 99%